FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI DI PROVINSI NUSA TENGGARA TIMUR - Tanebeth, Lorensa Aldayanti; Tameno, Nikson (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 6 (2024): Vol.13.No.6. JUNI.2024 [393-451]DO - 10.24843/EEP.2024.v13.i06.p02, 2024)
This research was conducted with the aim of knowing the effect of road infrastructure, gross regional domestic product (GRDP), district/city minimum wages (UMK) and the number of tourist visits on investment in East Nusa Tenggara Province in 2017-2019. The dependent variable in this research is investment and the independent variables in this study are road infrastructure, gross regional domestic product (GDP), district/city minimum wage (UMK) and the number of tourist visits. The data used in this study is secondary data collected by documentation techniques with data sources from the Central Bureau of Statistics of East Nusa Tenggara. This study uses a quantitative approach, which is then analyzed using the panel data regression method using the Eviews 9 application. The results of this study indicate that partially the infrastructure and GRDP per capita variables have no effect on investment, but the MSE and the number of tourist visits have a significant effect on investment in East Nusa Tenggara Province and simultaneously or together the infrastructure variables, GRDP per capita, UMK and the number of tourist visits have an influence on investment in East Nusa Tenggara in 2017-2019. Keywords : Investment, GRDP percapita, UMK, number of tourist visits .